The growth response of Pinus caribaea mor. var. hondurensis bar and golf seedlings to fertilizer application on the Serdang soil series - Manikam, Doraisingam; Srivastava, P.B.L. (1980)
A 33 × 2 factorial, soil bioassay experiment was conducted to study the effect of nitrogen, phosphorus, potassium and magnesium on the growth of Pinus caribaea var. hondurensis seedlings on the Serdang soil series. Nitrogen was applied at levels equivalent to 0 and 112 kg/ha; phosphorus and potassium, 0, 336.2 and 560.4 kg/ha and magnesium, 0, 67.2 and 112 kg/ha. The study was carried out over a period of 6 months. The height of the seedlings was measured at regular intervals of 2 weeks. At the end of the experimental period, the collar diameter, shoot, root and total plant weights were determined. The study showed that phosphorus was the most important single nutrient required by P. caribaea on this soil type. P and PK effects contributed significantly to height growth. The 336.2 kg/ha level of P was more effective than the 560.4 kg/ha level. N, P and NP promoted radial growth, while for dry matter production, only N and P were important. For radial growth and dry matter production, the 560.4 kg/ha level of P was more effective. Potassium and magnesium, either alone or together, inhibited growth, especially that of the shoot, but this effect was not prominent when phosphorus was also added. © 1980.